Segregação racial na orla de Belém: os portos públicos da Estrada Nova e o Ver-o-Peso - PEIXOTO, Rodrigo Corrêa Diniz (Museu Paraense Emílio Goeldi, 2017)
The municipal government, through urban developments, plans to gentrify public spaces in Belém´s waterfront. Gentrification here means to transform public spaces into consumption places, leading to the removal of people and, with them, the sociability that gives identity to these places. Public spaces focused here are the ports of Palha and Açaí and the Ver-o-Peso market. They are important places for popular life in Belém, mostly for the black people who use them. Thousands of people comute daily between these places in the continent and the many islands on the other side of the river. Gentrification tends to remove these people, most of them poor, and their activities to more distant areas. As the popular saying goes, ‘poverty has a color’. People resist urban developments that exclude black people. Nevertheless, racial factor isn’t acknowledged as contributing to segregation nor the racial argument is present in resistance discourse. Put together the cultural dimension and the racial factor recognized they would add significant weight to the capacity of resistance and insurgence among this population affected by the changes. This is a point the article raises.